OPTIMIZATION OF TECHNOLOGICAL PARAMETERS FOR THE FORMATION AND TRANSPORTATION OF MATERIAL FLOWS IN DEEP OPEN-PIT MINES - Norova Khurshida Yunusovna; Mukhiddinov Khusniddin Oybek ugli (Journal Park Publishing, 2025)
The article examines issues related to the management of technological parameters of material flows in the development of ore deposits by deep open-pit mining. It is shown that as the depth of mining operations increases, the share of costs for the transportation of rock mass reaches 80% or more, which leads to a reduction in the rate of pit deepening. The aim of the study is to improve the efficiency of open-pit haulage flows by enhancing methods of operational control and ore quality blending. The obtained results make it possible to justify rational technological parameters of transport schemes and can be used in the design and operation of automated mining management systems in deep open pits.
Keywords: deposit, open pit, haulage flow, parameter, ore, quality, reserves, resource, mining operations, rock mass, reserves, technogenic formation, sampling, mining system.